HDL and endothelial protection. (16th May 2013) - Tran‐Dinh, A; Diallo, D; Delbosc, S; Varela‐Perez, L Maria; Dang, QB; Lapergue, B; Burillo, E; Michel, JB; Levoye, A; Martin‐Ventura, JL; Meilhac, O
<x xml:space="preserve">Abstract</x> High‐density lipoproteins (HDLs) represent a family of particles characterized by the presence of apolipoprotein A‐I (apoA‐I) and by their ability to transport cholesterol from peripheral tissues back to the liver. In addition to this function, HDLs display pleiotropic effects including antioxidant, anti‐apoptotic, anti‐inflammatory, anti‐thrombotic or anti‐proteolytic properties that account for their protective action on endothelial cells. Vasodilatation via production of nitric oxide is also a hallmark of HDL action on endothelial cells. Endothelial cells express receptors for apoA‐I and HDLs that mediate intracellular signalling and potentially participate in the internalization of these particles. In this review, we will detail the different effects of HDLs on the endothelium in normal and pathological conditions with a particular focus on the potential use of HDL therapy to restore endothelial function and integrity.